The Predictive Role of Maladaptive Schemas in Chronic Pain of Adolescents - Saghar Salari; Maryam Shaygan; Giti Setoodeh; Parvin Ghaemmaghami (Journal of Pediatrics Review)
Background: Chronic pain is a prevalent issue among adolescents, negatively impacting various aspects of their lives. Objectives: To better understand the factors influencing adolescent pain, this study aimed to explore the predictive significance of maladaptive schemas concerning chronic pain. Methods: A total of 1,302 adolescents aged 12-21 years old were randomly selected from Shiraz, Iran, to participate in this study. Screening questions aligned with the 11th revision of the international classification of diseases (ICD-11) were used to identify adolescents with chronic pain. The young’s schema questionnaire-short form (YSQ-SF) was utilized to evaluate maladaptive schemas. Hierarchical logistic regression analysis was performed to investigate the contributions of various variables in predicting chronic pain. Results: The hierarchical logistic regression analysis revealed a significant contribution of the “disconnection/rejection” domain (OR=0.997, P=0.004) in predicting chronic pain. Additionally, maternal chronic pain (OR=0.878, P=0.008) was a predictor in this model. Conclusions: The results suggest that maternal chronic pain can be a predictor of chronic pain in adolescents. Furthermore, the “disconnection/rejection” domain was identified as a notable predictor of chronic pain in this age group.